Bina Desa Sadar Hukum Sejak Dini Di Desa Simpang Naneng Kecamatan Karusen Janang Kabupaten Barito Timur - Sijabat, Anjely; Silalahi, Hanna Yesica; Sitanggang, Marsella; Sinurat, Ririn Ribkha Elfani; Sari, Widayanti Nur Indah; Jalianery, Joanita; Sangalang, Rizki Setyobowo (Utami Publisher, 2025)
The early-stage legal awareness village program is an effort to enhance public legal awareness, particularly in Simpang Naneng Village, Karusen Janang District, East Barito Regency. This program aims to build community understanding of laws and citizens' rights to create an orderly and law-abiding environment. The methods used include legal socialization, group discussions, and practical training. The program's results indicate increased legal awareness and active participation in daily legal compliance. This initiative is expected to serve as a community empowerment model supporting sustainable and equitable village development.